1998
DOI: 10.1089/cbr.1998.13.351
|View full text |Cite
|
Sign up to set email alerts
|

Combined Modality Radioimmunotherapy with Taxol and 90Y-LYM-1 for Raji Lymphoma Xenografts

Abstract: Despite effective therapies for non-Hodgkin's lymphoma (NHL), the majority of patients are not cured. Radioimmunotherapy (RIT) has shown good results in preclinical and clinical trials even in patients that are non-responsive to standard chemotherapy. To make RIT more effective, agents such as paclitaxel (Taxol), that can enhance radiation effects, are being tested. Nude mice bearing human Burkitt's lymphoma (Raji) xenografts were treated with: 1) 150 or 200 microCi (5.5 or 7.3 MBq) of 90Y-2IT-BAD-Lym-1 alone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…In contrast, we, and others, have examined methods to increase radiosensitivity of the tumor, particularly with the application of chemotherapeutic drugs that may provide antitumor effects in and of themselves. Indeed, several preclinical studies of various tumor types (colorectal, 48 -51 breast, 52-54 medullary thyroid [55][56][57] and the more radiosensitive hematologic cancers 58,59 ) have examined this issue, with the majority reporting enhanced antitumor activity of the combined treatment modality as compared to either treatment arm alone. To date, clinical experience in solid tumors is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we, and others, have examined methods to increase radiosensitivity of the tumor, particularly with the application of chemotherapeutic drugs that may provide antitumor effects in and of themselves. Indeed, several preclinical studies of various tumor types (colorectal, 48 -51 breast, 52-54 medullary thyroid [55][56][57] and the more radiosensitive hematologic cancers 58,59 ) have examined this issue, with the majority reporting enhanced antitumor activity of the combined treatment modality as compared to either treatment arm alone. To date, clinical experience in solid tumors is limited.…”
Section: Discussionmentioning
confidence: 99%
“…90 Y-DOTA-peptide-Lym-1 was prepared as previously described. 43 Assessment by high-performance liquid chromatography (HPLC), thin-layer chromatography (TLC), and cellulose acetate electrophoresis revealed that 90 Y-DOTA-peptide-Lym-1 was prepared to 98% radiochemical purity with less than 5% aggregate content.…”
Section: Reagentsmentioning
confidence: 99%
“…Multiple preclinical and clinical studies with sodium iodine-131( 131 I), copper-67 ( 67 Cu), and yttrium-90 ( 90 Y)-labeled Lym-1 have demonstrated significant efficacy in relapsed and refractory NHL. 8,9,[17][18][19][20] In an MTD trial in which heavily pretreated NHL patients were treated with 131 I-Lym-1, 85% had tumor regression, and 19% achieved complete response (CR). 8 Combined modality therapy (CMT) consists of the concurrent or sequential use of chemotherapy and external beam radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another approach, radiolabeled chemotherapy agents have been used in an attempt to enhance cytotoxicity in both human cancer cells and apparently normal hamster fibroblasts (5). Chemotherapy has also been combined with radioimmunotherapy (6).…”
mentioning
confidence: 99%